Skaldic verse and the poetics of saga narrative - O'Donoghue, Heather (Oxford University Press, 2005)
This work provides a detailed reading of a series of sophisticated medieval narratives, the Old Norse-Icelandic sagas. It shows how saga authors achieved a wide range of stylistic and pyschological effects through the interplay of prose and verse.
10.1093/acprof:oso/9780199267323.001.0001
Keywords: Old Norse poetry; Scalds and scaldic poetry